A novel virtual resource pricing policy based on game model in federated clouds. (3rd March 2020) - Tian, Yuan
In recent years, more and more cloud providers are unified together to form a federated cloud market, where a suitable pricing strategy plays a key role to help they attracting more users. However, many existing pricing policies can not deal with the competition between different cloud providers. In this study, we take efforts on the resource pricing policy in federated cloud market. To obtain an optimal pricing scheme among multiple IaaS providers (ISPs), we firstly use the learning curve model to model the production supply behaviours of ISPs, and then we use a standard Markov decision process to describe the pricing game model and present an efficient algorithm to solve this game model in a distributed manner. The proposed pricing model has been fully investigated and evaluated in a real-world federated cloud platform, and the results indicate that it can significantly improve the profits of ISPs comparing to several existing pricing mechanisms.